A phenomenological study on working dual jobs among women from the federal government's offices in the state of Sabah, Malaysia - Aslynda Jane Mohd Afsur Khan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research aims to analyse the experiences and feelings of the women participants on working dual jobs. 10 participants were selected among women employees from eight Federal Government Offices of Sabah State, Malaysia. The said offices were located at Kompleks Pentadbiran Kerajaan Persekutuan Sabah, Jalan Sulaman Likas, Kota Kinabalu, Sabah, Malaysia, which was the central administration offices for the Federal Government of Sabah. This research used a phenomenological method of three-part interviews with the participants. The findings discovered six types of job scope indicated by participants as their second/other jobs namely accounting; multi-level marketing (MLM); skin care product; teaching; tourism; and catering. Theory of Rational Choice (TRC) was the theoretical framework used for this research. The original TRC confirmed that additional income, financial security and financial independent as the determinants on working dual jobs. Interestingly, these current findings presented six new factors/determinants that included: 1) having family responsibility; 2) having fun due to passion and hobby; 3) succumbing to employer's command; 4) receiving spouse's blessing and encouragement; 5) deriving from one's own self-motivation; and 6) wanting to be independent. In short, this present empirical research has not only confirmed the original TRC, it has also constructively extended its application, which significantly contributed to a new dimension about the dual jobs phenomenon among working women.